Marketing Adoption Among Small and Medium Scale Malay Entrepreneurs in Peninsular Malaysia - Yacob, Nik Rahimah (The International Journal of Accounting and Business Society, 1996)
This study exmines the influence of external, internal and organization factors on marketing adoption among small and medium scale Maly entrepreneurs in Peninsular Malaysia. Marketing Adoption was operationalised as a firm behavior manifested by the number of marketing activities being carried out by the entrepreneur. From a survey of 249 Malay entrepreneurs in the manufacturing and service sectors, it was found that the three external factors of demand condition, competitiveness, and seasonally player an insignificant role in explaining the different levels of marketing adoption by the entrepreneus. Similarly, the tree internal factor of business aspiration, marketing importance, and business success also failed to exertÂ  a significant influence on marketing adoption. The only significant antecedent of marketing adoption was that of business sector suggesting that Malay entrepreneurs tended to crarry out a set marketing activities that seemed to be dominant in a particular sector.